The good use of NSAID: when, why and how - Gianluca Conversa (Publiediting, 2019)
Non-steroidal anti-inflammatory drugs (NSAIDs) are the first line treatment of acute or recurrent pain and often remain the prerogative of the primary care physician if not the patient himself on self-administration. The beneficial and side effects are widely known, however in recent years scientific evidence has made new and interesting contributions that deserve to be made known also and especially in the specialistic field. Rational use and patient selection criteria are important to optimize clinical outcome and minimize risk.